Insight guides : pakistan - Guides, Insight ([S.l.] : Insight Guides, 2007)
The Insight Guide to Pakistan provides the complete picture through expert and informative text and remarkable photography. It is an inspiring background read, serving as an invaluable, on-the-spot companion - but can also be kept as a superb, visual souvenir of a visit. Expert local writers bring to life each destination's history, culture, arts and people. It contains detailed, cross-reference maps which means that areas and sites mentioned can be quickly pin pointed. A new section highlights the best of Pakistan and section of Travel Tips incorporates all the travel details and contact numbers visitors will need.